(Lu0.3Gd0.7)2SiO5:Y3+ single crystals grown by the laser floating zone method: structural and optical studies. Issue 45 (7th November 2018) - Rey-García, F.; Rodrigues, J.; Fernandes, A. J. S.; Soares, M. R.; Monteiro, T.; Costa, F. M.
Abstract : Laser floating zone growth of transparent Y0.05:(Lu0.3Gd0.7)2SiO5 single crystals suitable as laser host materials. Abstract : Highly transparent (Lu0.3 Gd0.7 )2 SiO5 :Y 3+ (5 at%) single crystals were obtained by the laser floating zone (LFZ) technique in air at 10 mm h −1 . Scanning electron microscopy (SEM/EDS) allowed observation of homogeneous crystalline fibres of B-type oxyorthosilicates with a C 2/ c monoclinic structure, as revealed by X-ray diffraction and Raman spectroscopy studies. Optical measurements on 0.32 mm thick samples revealed ∼86% transmission in the visible-NIR range, together with intense intra 4f 7 transitions of Gd 3+ ions from the 8 S7/2 ground state in the UV region. Additionally, as a good indication of being a host matrix for photonic applications, a wide bandgap favouring the introduction of energy levels in the forbidden band was observed in these materials through photoluminescence (PL) and photoluminescence excitation (PLE) studies.